Mobile money: the challenge of payments for the unbanked - Murphy, Alix (Henry Stewart Talks, 2018)
This case study examines the growth of mobile money in the early 2000s and explores the circumstances of personal and business life in developing economies that made this technology so successful. It looks in particular at two examples of mobile money in the Philippines and Kenya.